1982
DOI: 10.1007/bf01657676
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cholangiography and ultrasonography in the operative screening of the common bile duct

Abstract: Operative cholangiography and operative real‐time, B‐mode ultrasound scanning were compared as the initial screening tests for calculi in the common bile duct. On the basis of experience at 150 operations, the 2 tests were comparable in terms of sensitivity, specificity, efficiency, and predictability of a negative test. Ultrasound was associated with a higher predictability of a positive test than was cholangiography. However, this difference was not significant. Operative Ultrasonography appears to match the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 6 publications
1
8
1
Order By: Relevance
“…Compared to operative cholangiography, OUS demonstrates equal or superior accuracy [5,6,20]. In our study, the predictability of a positive test of OUS was significantly higher, likely contributing to the high positive common bile duct exploration rate.…”
Section: Discussionmentioning
confidence: 63%
“…Compared to operative cholangiography, OUS demonstrates equal or superior accuracy [5,6,20]. In our study, the predictability of a positive test of OUS was significantly higher, likely contributing to the high positive common bile duct exploration rate.…”
Section: Discussionmentioning
confidence: 63%
“…The main purpose of these operative diagnostic procedures, in the setting of verified or suspected cholelithiasis, is to detect common bile duct disease that would not otherwise be suspected. Consideration of data gathered in the present large series of patients and in the patients followed by Sigel et al [24] lead to the conclusion that both methods are reliable, but operative sonography in experienced hands is more accurate. Both studies, using similar methods of comparison and analysis of these imaging procedures, offer a similar conclusion.…”
Section: Discussionmentioning
confidence: 69%
“…Interest in this method increased in the early 1980s when several studies showed that intraoperative ultrasound was equal or superior to static IOC for detecting choledocholithiasis [15,20,21], but the technique was never widely accepted. During the OC era, the major role of intraoperative imaging was detection of CBDS, whereas during the era of LC, a greater emphasis has been placed on the role of these imaging methods in identifying anatomic variations and detecting stones.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in the early 1980s showed that intraoperative ultrasound was as accurate as intraoperative cholangiogram (IOC) for detecting choledocholithiasis during OC [15,20,21]. The advent of laparoscopic ultrasound (LUS) in the early 1990s sparked interest in this method of bile duct imaging during LC.…”
Section: Introductionmentioning
confidence: 99%